2006
DOI: 10.3168/jds.s0022-0302(06)72263-9
|View full text |Cite
|
Sign up to set email alerts
|

The Linear Relationship Between the Proportion of Fresh Grass in the Cow Diet, Milk Fatty Acid Composition, and Butter Properties

Abstract: Fresh grass in the cow diet improves the rheological and nutritional properties of butter. However, the relationship between the proportion of fresh grass in the diet and these properties is still unknown. The objective of the study was to determine the relationship between the proportion of fresh grass in the diet and the properties of milk and butter. Four groups of 2 cows were fed 4 isoenergetic diets characterized by increasing amounts of fresh grass (0, 30, 60, and 100% dry matter of forage) according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
259
6
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 274 publications
(325 citation statements)
references
References 22 publications
49
259
6
11
Order By: Relevance
“…The effect of diet on the FA profile is consistent with the literature (Chilliard et al, 2001;Hurtaud et al, 2002;Schroeder et al, 2003;Couvreur et al, 2006a and. The large increase in C18:1 is probably due to a greater mobilization of the lipidic reserves with the LowGS diet (Chilliard et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…The effect of diet on the FA profile is consistent with the literature (Chilliard et al, 2001;Hurtaud et al, 2002;Schroeder et al, 2003;Couvreur et al, 2006a and. The large increase in C18:1 is probably due to a greater mobilization of the lipidic reserves with the LowGS diet (Chilliard et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…This result is in agreement with Timmen and Patton (1988), Fauquant et al (2005), Rahmatyar and Wiking (2012) and Mesilati-Stahy and Argov-Argaman (2014) who have shown that the small MFG, in comparison with the large MFG from the same milk, have higher contents in PUFA, MUFA and lower contents in short SFA (de novo synthesized). This result could be partly linked to the feeding treatments reported in SMFG group (grazing, lipid supplementation mainly) as shown by Couvreur et al (2006) and Lopez et al (2014) with a pasture-based diet or by Hurtaud et al (2010) with a maize silage-based diet supplemented with extruded linseed. Moreover, FA profile differences between LMFG, MFGM milk and MFGM yield milk are weak.…”
Section: Discussionmentioning
confidence: 94%
“…The relevant factors reported in the literature are the diet composition (forage composition, lipid supplementation), the breed or the individual variability. For instance, the average MFG diameter is 0.3 µm lower in Holstein cows (3.3 µm) in comparison with Normandy cows (3.6 µm) Logan et al, 2014); in comparison with a maize silage-based diet, it decreases down to 0.3 to 0.4 µm when cows are fed on pasture (3.4 v. 3.1 µm, respectively) or on a supplemented maize silage diet with linseed oil (4.2 v. 3.8 µm, respectively) (Couvreur et al, 2006 andHurtaud et al, 2010;Lopez et al, 2014) and down to −0.2 µm with high-concentrate low-forage diets . It is modulated by the lactation stage (Mesilati-Stahy and Argov-Argaman, 2014; Altenhofer et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…In deviation to these findings butter from the prairie land in Normandy showed similar values to butter from mountainous areas. Couvreur et al [14] found a linear positive relationship between the proportion of fresh grass in the cows' diet and the concentration of unsaturated fatty acids, as well as the concentration of CLA, with +0.38 and +0.12%, respectively, per +10% of fresh grass. In their recent review on the variation of CLA in unprocessed milk fat, Collomb et al [13] report values ranging from 0.2 to 5.37 g·100 g -1 fat.…”
Section: Introductionmentioning
confidence: 99%